Sex Differences in Outcome and Prescribing Practice in ST-elevation MI Patients with Multivessel Disease and Incomplete Revascularisation - Sonya Burgess; Craig P Juergens; Wesley Yang; Ibrahim M Shugman; Hanan Idris; Tuan Nguyen; Alison McLean; Sarah Zaman; Liza Thomas; Kristy P Robledo; Christian Mussap; Sidney Lo; et al. (European Cardiology Review, 2023)
Objective: To investigate the extent to which multivessel disease, incomplete revascularisation and prescribing differences contribute to sex-based outcome disparities in patients with ST-elevation MI (STEMI) and establish whether differences in cardiac death and MI (CDMI) rates persist at long-term follow-up. Methods and results: This observational study evaluates sex-based outcome differences (median follow-up 3.6 years; IQR [2.4–5.4]) in a consecutive cohort of patients (n=2,083) presenting with STEMI undergoing percutaneous coronary intervention). Of the studied patients 20.3% (423/2,083) were women and 38.3% (810/2,083) had multivessel disease (MVD). Incomplete revascularisation was common. The median residual SYNTAX score (rSS) was 5.0 (IQR [0–9]) in women and 5.0 (IQR [1–11]) in men (p=0.369), and in patients with MVD it was 9 (IQR [6–17]) in women and 10 (IQR [6–15]) in men (p=0.838). The primary endpoint CDMI occurred in 20.3% of women (86/423) and in 13.2% of men (219/1,660) (p=0.028). Differences persisted following multivariable risk adjustment: female sex was independently associated with CDMI (aHR 1.33; IQR [1.02–1.74]). Women with MVD had CDMI more often than all other groups (p<0.001 for all). Significant sex-based prescribing differences were evident: women were less likely to receive guideline-recommended potent P2Y12 inhibitors than men (31% versus 43%; p=0.012), and differences were particularly evident in patients with MVD (25% in women versus 45% in men, p=0.011). Conclusion: Sex-based differences in STEMI patient outcome persist at long-term follow-up. Poor outcomes were disproportionately found in women with MVD and those with rSS>8. Observed differences in P2Y12 prescribing practices may contribute to poor outcomes for women with MVD and incomplete revascularisation.